Fitness profiles of professional futsal players: identifying age-related differences - Sekulic Damir; Gilic Barbara; Foretic Nikola; Spasic Miodrag; Uljević Ognjen; Veršić Šime (Sciendo, 2020)
Study aim: The aim of this study was to determine the fitness profiles of senior and junior futsal players and to identify potential differences between the studied age groups.